(untitled) (Zoological Records and Reviews, 2026)
Soil invertebrates constitute the most diverse and functionally critical component of tropical terrestrial ecosystems, driving nutrient cycling, organic matter decomposition, soil structure formation, and energy flow through food webs. Despite their ecological importance, the diversity and community composition of tropical soil invertebrate fauna remains substantially less documented than above-ground communities in the same ecosystems. This study presents a comprehensive assessment of soil invertebrate diversity across three tropical land-use types – primary forest, secondary forest, and converted agricultural land – in the Western Ghats of India, the Atlantic Forest margin of Brazil, and the Congo Basin of Cameroon, using standardised soil core sampling, Berlese-Tullgren extraction, pitfall trapping, and Winkler litter extraction at 54 sites surveyed during wet and dry seasons. A total of 1,842 soil invertebrate morphospecies from 28 orders and 184 families were recorded across all sites, dominated by Collembola (428 morphospecies), Acari (384morphospecies), Coleoptera (312 species), and Formicidae (224 species). Species richness and community composition differ significantly among land-use types, with primary forest supporting 48.4% more morphospecies than agricultural land. Land-use conversion is associated with a significant shift in community composition from specialist forest-interior species to generalist disturbance-tolerant taxa. Soil organic matter content, moisture, and litter depth are the three strongest predictors of soil invertebrate diversity. Results confirm that primary tropical forest soils support irreplaceable invertebrate diversity that cannot be restored by secondary forest succession on ecologically relevant timescales.